42nd Winter School on Vibroacoustical Hazards Suppressions - BUKOWSKI, Roman (Archives of Acoustics, 2014)
Traditionally, the 42nd Winter School on Vibroacoustical Hazards Suppressions national conference is organized by Upper Silesian Division of the Polish Acoustical Society. The conference again is organized in Szczyrk. As at previous year, the conference has two coorganizers, i.e. Institute of Physics – Science-Didactic Center at the Silesian University of Technology and the Committee on Acoustics of the Polish Academy of Sciences.